Closure - Management, Journal of Infrastructure & Facility Asset (Journal of Infrastructure & Facility Asset Management, 2025)
Journal of Infrastructure & Facility Asset ManagementVolume 7, Special Issue 3, January 2025                                 (e) ISSN 2656-8896  (P) ISSN 2656-890X Volume 7, Special  Issue 2, January 2025Handling Selection of Compression And Stability Problems of Embankment Based on The Thickness of Soft Soil Layer Below (Case Study: Rengat – Pekanbaru Toll Road Project Sta. 176+775 – Sta. 176+975) Pandu Hermawan, Noor Endah Mochtar, Indrasurya B. Mochtar, & Mahar Muliawan Slope Stability Analysis Under Dry-Wetting Cycle Conditions (Case Study: Landslide Countermeasure of Batas Pidie/Aceh Besar - Batas Kota Sigli) Zulfadhli, Trihanyndio Rendy Satrya, Ria Asih Aryani Soemitro & Fikri Afzal Alternative Planning Slope Stabilization On Roadway Case Study : Landslide On Tabone-Polewali Road Section KM 168+790 to 168+820 Ismi Istiqamah, Mohamad Khoiri, Mahendra Andiek Maulana & Bambang S. RazakStudy of The Behavior of Abutment Piled Foundation due to Nearby Staged-Embankment (Case Study: Kali Kandang Bridge on The North Ring Road of Lamongan) Azkiya Nabila, Trihanyndyo Rendy Satrya, Ria Asih Aryani Soemitro, Sifa Udukha Behaviour Study of Abutment Pile Foundation on Lightweight Embankment Oprit Nila Wahyu Pertiwi, Ria Asih Aryani Soemitro, Trihanyndio Rendy Satrya, Sifa' UdukhaVolume 7, Special  Issue 1, January 2025Parametric Study of Embankment Stability And Geotextile Reinforcement On Soft Soil Mirza Syah Alam, Herman Wahyudi, Yudhi Lastiasih, Yusrizal Kurniawan Analysis Of Slope Stability Based On The Effect Of RainFall On The Lombok International Airport (Bil) – Mandalika Road STA 10+375 to STA 10+550 Made Sudiadnya, Mohamad Khoiri, Dwa Desa Warnana, Herlambang Zulfikar Analysis of The Effect of Seismic Load on The Design Safety Factor of Foam Mortar with Bored Pile Landslide Location of Batas Pidie/Aceh Besar – Bts. Kota Sigli STA 0+560 Ichvan Danny Kurniawan, Trihanyndio Rendy Satrya, Ria Asih Aryani Soemitro, Fikri Afzal A Study of Pile Displacement in Soft Soil: The Case of Semarang - Demak Toll Road Construction Package 1B Novera Sagita, Herman Wahyudi, Yudhi Lastiasih &Yusrizal Kurniawan Design Of Toll Road Embankment With Secondary Compression Mitigation After PVD Installation And Solutions For The Probolinggo – Banyuwangi Toll Road Construction Project PackKAGE 2 STA 16+300 – STA 16+700 Septya Kukuh Aryandi, Indrasurya B. Mochtar, Noor Endah, Abdjad Agung Artanto